Essentials of Math with Business Applications - Nelson Marceda (Mc Graw Hill, 2007)
This text is organized into 60 distinct Skill Builders meant to prepare students with the skills and competencies they will need to enter the workforce or to go into business careers. Students gain real-world math skills by working business problems and applications involving interest, discounts, payroll, depreciation, retail selling, and checking accounts.